Heat-resistant alloy having nitriding resistance

JP2025024024AInactive Publication Date: 2025-02-19KUBOTA CORP

Patent Information

Application Number
JP2024194842
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-05-10
Filing Date
2024-11-07
Publication Date
2025-02-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0019】 本発明に係る耐熱合金は、耐窒化性にすぐれ、また、高温クリープ破断強度にすぐれる。従って、500℃以上の高温で使用されるアンモニアガス熱分解装置の分解管に好適である。分解管は、とくに、高圧プロセスで使用されるアンモニアガス熱分解装置への適用が好適であり、大量生産設備による体積の低減や発電用途などの後流プロセスへの供給に有利である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024024000001_ABST
    Figure 2025024024000001_ABST
Patent Text Reader

Abstract

To provide a heat-resistant alloy having nitriding resistance and high-temperature creep rupture strength.SOLUTION: A heat-resistant alloy contains, in mass%, C: 0.2-0.6%, Si: more than 0% but not more than 2.5%, Mn: more than 0% but not more than 2.0%, P: 0.03% or less, S: 0.03% or less, Ni: 33.0-50.0%, and Cr: 24.0-50.0%, with the balance being Fe and impurities. The heat-resistant alloy may also contain, optionally, Nb: more than 0% but not more than 1.8%; optionally, rare-earth element: more than 0% but not more than 0.5%; optionally, Ti: more than 0% but not more than 0.5% and / or Zr: more than 0% but not more than 0.5%; and optionally, W: more than 0% but not more than 2.0%, and / or Mo: more than 0% but not more than 0.5%.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-resistant alloy having excellent nitriding resistance. [Background technology]

[0002] Decarbonization is required to achieve carbon neutrality. Hydrogen gas is attracting attention as a next-generation energy source that does not emit carbon dioxide. However, there are challenges in storing and transporting hydrogen gas safely and efficiently.

[0003] For this reason, hopes are pinned on ammonia. Ammonia is a hydrogen carrier with high hydrogen density, and is easy to liquefy, transport, and store, allowing for stable imports from overseas. This ammonia can be used as fuel because it can be burned without being decomposed, but hydrogen gas obtained by thermally decomposing ammonia is often used in hydrogen power generation turbines, fuel cells, hydrogen reduction steelmaking, and other technologies. For this reason, it is extremely useful to produce hydrogen by thermally decomposing ammonia.

[0004] Patent Document 1 discloses an ammonia gas thermal decomposition device that uses a catalyst. In this ammonia gas thermal decomposition device, ammonia gas that has been heated to about 300°C to 700°C in advance is introduced into a reactor that contains a catalyst, whereby the ammonia gas is thermally decomposed into hydrogen gas and nitrogen gas. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2022-109042 Summary of the Invention [Problem to be solved by the invention]

[0006] Ammonia gas generates nitrogen atoms through thermal decomposition, which diffuse into the alloy that makes up the cracking tube and cause it to nitride. For this reason, the heat-resistant alloy that makes up the cracking tube must be resistant to nitridation. In general, Al, Cr, Mo, and Ti are elements that easily combine with nitrogen to form nitrides, and the higher the Ni content, the more difficult it is to cause nitridation.

[0007] For example, in nitriding equipment (gas nitriding furnaces) that perform gas nitriding of metals, stainless steels and Ni-based alloys with high Ni content are used as furnace materials.

[0008] It is desirable for the hydrogen production process by ammonia decomposition to be a high-pressure process. This is because it is advantageous for reducing the volume of mass production facilities and for supplying the hydrogen to downstream processes such as power generation. High pressure here means a pressure of more than about 1.0 MPa, and the higher the pressure, the more desirable it is. However, to operate at high pressure, the cracking tube must have high-temperature creep rupture strength.

[0009] An object of the present invention is to provide a heat-resistant alloy which is excellent in nitridation resistance and high-temperature creep rupture strength. [Means for solving the problem]

[0010] The heat-resistant alloy of the present invention is In mass%, C: 0.2% to 0.6%, Si: more than 0% and not more than 2.5% Mn: more than 0% and not more than 2.0% P: 0.03% or less, S: 0.03% or less, Ni: 33.0%~50.0%, Cr: 24.0%~50.0%, The balance is Fe and impurities. Optionally, Nb: more than 0% and not more than 1.8%; Optionally, rare earth elements: more than 0% but not more than 0.5%; Optionally, Ti: more than 0% but not more than 0.5% and / or Zr: more than 0% but not more than 0.5%; Optionally, W: more than 0% to 2.0% and / or Mo: more than 0% to 0.5%.

[0011] The above heat-resistant alloy is C: 0.45%~0.55%, Si: over 0% and not more than 1.5% Ni: 33.0%~50.0%, Cr: 24.0%~27.0% Nb: more than 0% and 1.0% It is preferable that:

[0012] The above heat-resistant alloy is C: 0.4%~0.6%, Si: over 0% and not more than 2.0% Ni: 40.0%~50.0%, Cr: 24.0%~38.0%, Nb: 0.5% to 1.8%; It is preferable that:

[0013] The above heat-resistant alloy is C: 0.2%~0.5%, Ni: 40.0%~50.0%, Cr: 30.0% to 50.0%; Optionally, Ti: more than 0% and not more than 0.4%; It is preferable that:

[0014] The creep rupture strength of the above heat-resistant alloy is desirably 20 MPa or more at 900°C for 1000 hours.

[0015] It is desirable for the activation energy of nitrogen diffusion in the heat-resistant alloy to be 35 kJ / mol or more.

[0016] The heat-resistant alloy is preferably a centrifugally cast product.

[0017] The above heat-resistant alloys are suitable for use in high-temperature environments of 500° C. or higher.

[0018] The cracking tube for an ammonia gas thermal cracking apparatus of the present invention comprises: It may be formed from the heat resistant alloys described above. Effect of the Invention

[0019] The heat-resistant alloy according to the present invention has excellent nitriding resistance and high-temperature creep rupture strength, and is therefore suitable for use as a cracking tube in an ammonia gas thermal cracking device used at high temperatures of 500°C or higher. The cracking tube is particularly suitable for use in an ammonia gas thermal cracking device used in a high-pressure process, and is advantageous for reducing the volume of mass production facilities and for supplying the tube to downstream processes such as power generation. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a photograph of a cross section of the structure of the test piece of Comparative Example 1. [Diagram 2] FIG. 2 is a graph plotting the creep rupture strength and nitride layer thickness of the test piece of the first example. [Diagram 3] FIG. 3 is a graph plotting the creep rupture strength and activation energy of the test specimen of the second example. [Figure 4] FIG. 4 shows EPMA images of the test pieces of Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, the embodiments of the present invention will be described in detail. In addition, unless otherwise specified, "%" means % by mass.

[0022] The heat-resistant alloy of the present invention, which has excellent nitriding resistance, is used, for example, as a cracking tube for an ammonia gas thermal decomposition device. The cracking tube is heated from the outside to 500°C to 1000°C in a non-catalytic environment while the raw ammonia gas flows through it. 2NH3 → N2+ 3H2 The pyrolysis shown in FIG. 1 is carried out to produce nitrogen gas and hydrogen gas.

[0023] The heat-resistant alloy of the present invention has the following properties: In mass%, C: 0.2% to 0.6%, Si: more than 0% and not more than 2.5% Mn: more than 0% and not more than 2.0% P: 0.03% or less, S: 0.03% or less, Ni: 33.0%~50.0%, Cr: 24.0%~50.0%, The balance consists of Fe and impurities.

[0024] The reasons for limiting the ingredients are explained below.

[0025] C: 0.2% to 0.6% C has the effect of improving castability and increasing high-temperature creep rupture strength. It also combines with Cr or selected elements such as Ti and Nb to form carbides, which increases high-temperature strength. For this reason, at least 0.2% is contained. However, if the content is too high, primary carbides of Cr7C3 tend to be formed widely, and secondary carbides are excessively precipitated during heat treatment, resulting in a decrease in ductility and toughness. For this reason, the upper limit is set to 0.6%. The lower limit of the C content is preferably 0.20% or 0.25%, and more preferably 0.30%. The upper limit of the C content is preferably 0.60% or 0.55%, and more preferably 0.50%.

[0026] Si: More than 0% and less than 2.5% Silicon is added as a deoxidizer for the molten alloy, and to increase the fluidity and oxidation resistance of the molten alloy. However, excessive addition of silicon leads to reduced ductility, reduced high-temperature creep rupture strength, poor surface quality after casting, and reduced weldability. For this reason, the upper limit of the silicon content is set at 2.5%. The preferred silicon content is 2.0%, and 1.7% is more preferred.

[0027] Mn: More than 0% and less than 2.0% Mn acts as a deoxidizer for the molten alloy, fixes S in the molten alloy, improves weldability, and is added to improve ductility. However, excessive addition of Mn leads to a decrease in high-temperature creep rupture strength and oxidation resistance, so the upper limit is set at 2.0%. The Mn content is preferably 1.5% or less.

[0028] P: 0.03% or less, S: 0.03% or less P and S are impurities that are inevitably mixed in during melting, and the amount of these impurities is allowed to be 0.03% or less. It is preferable that the amount of these impurities is small, and it is acceptable for it to be zero.

[0029] Ni: 33.0%~50.0% Ni is an element necessary for ensuring cyclic oxidation resistance and stability of metal structure, ensuring high-temperature creep strength, and stabilizing austenitization of heat-resistant alloys because of its excellent nitridation resistance. In addition, Ni contributes to improving high-temperature strength and oxidation resistance by adding it in combination with Cr or selectively added W, Ti, or Zr. It is also known as an element that contributes to improving nitridation resistance. This is because Ni hardly dissolves in Ni, and it is expected to have the effect of inhibiting the diffusion of nitrogen in the material. For this reason, at least 33.0% or more is contained. On the other hand, even if excessive Ni is added, the effect is saturated and it is also economically disadvantageous, so the upper limit is set to 50.0%. The lower limit of the Ni content is preferably 37.0%, and more preferably 40.0%.

[0030] Cr: 24.0%~50.0% Cr contributes to improving high-temperature strength and cyclic oxidation resistance. In addition, Cr, along with Ni and Fe, exhibits excellent heat resistance at high temperatures exceeding 1000°C. Furthermore, Cr bonds with C to form carbides, which have the effect of increasing high-temperature strength, and is expected to have the effect of pinning nitrogen atoms by forming fine nitrides and suppressing the growth of the nitride layer due to nitrogen diffusion. Therefore, the content is set at at least 24.0%. However, Cr is an element that easily bonds with N, and Cr carbides (Cr 23C in C6) is replaced with N, nitriding the alloy. In addition, since excessive production of Cr carbides and Cr nitrides leads to a decrease in ductility, a small content is preferable, with the upper limit being 50.0%. The lower limit of the Cr content is 24.0%, and the upper limit of the Cr content is 50.0%, with 46.0% being preferable, and 43.0% being more preferable.

[0031] Remainder Fe and impurities The balance is Fe and impurities. Impurities include impurities that are inevitably mixed in during melting. Fe is an element that promotes the penetration and diffusion of nitrogen into the material, and the less Fe, the better for nitridation resistance. Although it is the balance, Fe should preferably be 40.0% or less.

[0032] The heat-resistant alloy having the above-mentioned composition may selectively contain the following elements.

[0033] Nb: over 0% and up to 1.8% Nb is an element that easily forms carbides, and contributes to improving creep rupture strength and high-temperature tensile strength. Nb also contributes to improving aging ductility. As with Cr, Nb is expected to have the effect of pinning nitrogen atoms by forming nitrides and suppressing the growth of the nitride layer caused by nitrogen diffusion, which is effective in terms of nitridation resistance. Therefore, it is preferable to selectively include Nb. The lower limit of Nb is preferably 0.3%. On the other hand, excessive addition of Nb leads to ductility, so the upper limit is set to 1.8% or less, preferably 1.5% or less.

[0034] Rare earth elements (REM): over 0% and up to 0.5% REM refers to 18 elements, including 15 elements of the lanthanide series from La to Lu in the periodic table, plus Y, Hf, and Sc. The REM contained in the heat-resistant alloy can be mainly Ce, La, and Nd, and these three elements preferably account for about 80% or more of the total rare earth elements, more preferably about 90% or more. REM is desirably contained selectively because it dissolves in the base material and contributes to improving oxidation resistance. In order to exert these effects, when REM is added, it is preferable to contain an appropriate amount with the upper limit set at 0.5%.

[0035] Ti: more than 0% but not exceeding 0.5% and / or Zr: more than 0% but not exceeding 0.5% One or both of Ti and Zr are selectively added to improve oxidation resistance and high-temperature compressive creep strength. Ti is an element that easily forms carbides, and also contributes to improving high-temperature tensile strength. As with Cr, Ti is expected to pin nitrogen atoms by forming nitrides and inhibit the growth of the nitride layer caused by nitrogen diffusion, which is effective in improving nitridation resistance. Zr also has a denitrification effect. To obtain these effects, Ti and Zr can be selectively added. On the other hand, Ti is also an element that easily bonds with N, and may cause deterioration of castability due to a decrease in the fluidity of the alloy, and may also make machining difficult. Therefore, when Ti is added, the upper limit is set to 0.5%, preferably 0.3%. Zr reduces hot plastic workability (e.g. bending), so when Zr is added, the upper limit is set to 0.5%, preferably 0.4%.

[0036] W: more than 0% but not exceeding 2.0% and / or Mo: more than 0% but not exceeding 0.5% W and Mo are elements that dissolve in the base metal and have the same properties of strengthening the austenite phase of the base metal and improving the creep rupture strength, and either one or both can be selectively contained. However, excessive inclusion of W or Mo leads to a decrease in ductility and carburization resistance. Excessive inclusion of W or Mo also leads to a decrease in the oxidation resistance of the base metal, and Mo exerts twice the effect of W equivalently. Therefore, the upper limit when adding W is 2.0%, and the upper limit when adding Mo is 0.5%. The upper limit of W is more preferably 1.8%, and the upper limit of Mo is more preferably 0.4%.

[0037] Ta: 0%~0.5% Ta forms carbides with C, an inevitable impurity contained in Ni-based alloys, and refines the crystal grains in the Ni-based alloy to improve the high-temperature strength of the Ni-based alloy. It can also be selectively added to improve corrosion resistance. However, excessive inclusion can inhibit the workability of the Ni-based alloy and reduce its strength. Therefore, when Ta is added, the upper limit of its content is set to 0.5%, and 0.3 is more preferable.

[0038] In a specific embodiment, the heat-resistant alloy of the present invention comprises: C: 0.45%~0.55%, Si: over 0% and not more than 1.5% Mn: more than 0% and not more than 2.0% P: 0.03% or less, S: 0.03% or less, Ni: 33.0%~50.0%, Cr: 24.0%~27.0%, Nb: over 0% and not more than 1.0% The balance is Fe and impurities. Optionally, rare earth elements: more than 0% but not more than 0.5%; Optionally, Ti: more than 0% and not more than 0.5%; Optionally, W: more than 0% to 1.0% and / or Mo: more than 0% to 0.5%.

[0039] In a specific embodiment, the heat-resistant alloy of the present invention comprises: C: 0.4%~0.6%, Si: more than 0% and not more than 2.0% Mn: more than 0% and not more than 2.0% P: 0.03% or less, S: 0.03% or less, Ni: 40.0%~50.0%, Cr: 24.0%~38.0%, Nb: 0.5%~1.8% or less, The balance is Fe and impurities. Optionally, rare earth elements: more than 0% but not more than 0.5%; Optionally, Ti: more than 0% and not more than 0.5%; Optionally, W: more than 0% to 1.0% and / or Mo: more than 0% to 0.5%.

[0040] In a specific embodiment, the heat-resistant alloy of the present invention comprises: C: 0.2%~0.5%, Si: more than 0% and not more than 2.5% Mn: more than 0% and not more than 2.0% P: 0.03% or less, S: 0.03% or less, Ni: 40.0%~50.0%, Cr: 30.0%~50.0%, The balance is Fe and impurities. Optionally, Nb: more than 0% and not more than 1.8%; Optionally, rare earth elements: more than 0% but not more than 0.5%; Optionally, Ti: more than 0% and not more than 0.5%; Optionally, W: more than 0% to 1.0% and / or Mo: more than 0% to 0.5%.

[0041] The heat-resistant alloy of the present invention has excellent nitridation resistance. This is because the alloy contains a large amount of Ni, which is difficult to nitride, and forms a stable austenite phase. Also, the alloy does not contain a large amount of elements that easily bond with nitrogen atoms to produce nitrogen processed products. The nitridation resistance can be judged, for example, by the thickness of the nitride layer formed on the cast body in the nitriding environment shown in the examples.

[0042] Furthermore, since the heat-resistant alloy of the present invention contains the above-mentioned elements, it has a high activation energy for nitrogen diffusion and is excellent in nitridation resistance. This reduces the amount of nitrogen that penetrates into the casting in a nitriding environment, and prevents the nitrided layer from thickening. The activation energy for nitrogen diffusion is preferably 35 kJ / mol or more, more preferably 38 kJ / mol or more, and even more preferably 40 kJ / mol or more. Although a higher activation energy for nitrogen diffusion is preferable, referring to the second embodiment, the upper limit is 100 kJ / mol, and preferably 80 kJ / mol.

[0043] The activation energy of nitrogen diffusion was derived as follows. The heat-resistant alloy was exposed to nitriding atmospheres with different temperatures, and the diffusion coefficient D at each temperature was derived according to the parabolic law of diffusion. Next, an Arrhenius plot was created from the reciprocal of the temperature and the natural logarithm of the diffusion coefficient D. The activation energy of the heat-resistant alloy was derived from the slope of the Arrhenius plot. The diffusion coefficient D was derived by collecting data at multiple points in the range of 600°C to 950°C.

[0044] The heat-resistant alloy of the present invention has excellent creep rupture strength, particularly high-temperature creep rupture strength, due to the inclusion of C, Ni, and selectively Nb and Ti. When used as a cracking tube for an ammonia gas thermal cracking device, the creep rupture strength is preferably such that the rupture time is 1000 hours or more at a test temperature of 900°C and a stress of 20 MPa, more preferably such that the rupture time is 1000 hours or more at a test temperature of 900°C and a stress of 25 MPa, and more preferably such that the rupture time is 1000 hours or more at a test temperature of 900°C and a stress of 30 MPa.

[0045] The heat-resistant alloy of the present invention also has excellent castability. This is due to the optimized content of alloying elements such as Ni and Cr, and the composition design that takes into account the fluidity of the molten metal. Castings made of the heat-resistant alloy of the present invention can be produced by mixing the component elements so as to satisfy the above composition ranges, and by casting methods such as centrifugal casting and static casting.

[0046] As described above, the heat-resistant alloy of the present invention has excellent nitriding resistance, high-temperature creep rupture strength, and castability, and is therefore suitable for use in cracking tubes of ammonia gas thermal cracking apparatuses used in nitriding environments where high-pressure ammonia gas is supplied under high-temperature atmospheres of, for example, 500° C. Among these, cracking tubes made of the heat-resistant alloy of the present invention are suitable for use in ammonia gas thermal cracking apparatuses used in high-pressure processes, and are advantageous for reducing the volume of mass production facilities and for supplying the tubes to downstream processes such as power generation applications. EXAMPLES

[0047] <<First Example>> Cracking tubes having alloy compositions (unit: mass%, balance Fe and impurities) of Examples 1 to 3 and Comparative Examples 1 to 3 shown in Table 1 were produced by centrifugal casting, and castability was confirmed. Comparative Example 1 was made of SUS310S, Comparative Example 2 was made of Inconel 625 (registered trademark), and Comparative Example 3 was made of Hastelloy C276 (registered trademark).

[0048] [Table 1]

[0049] Test pieces were cut from each of the cracking tubes and subjected to creep rupture tests and ammonia exposure tests. The details of the tests are given below, and the results are shown in Table 2.

[0050] [Table 2]

[0051] The heat-resistant alloy of the present invention contains a slightly larger amount of carbon and silicon to optimize castability, and has superior castability compared to the materials listed as comparative examples. When manufacturing using centrifugal casting, it is desirable to have excellent castability, i.e., good fluidity, and it can be said that the heat-resistant alloy of the present invention is reasonable. The castability was evaluated in the second example.

[0052] In addition, the heat-resistant alloy of the present invention has excellent high-temperature oxidation resistance. Elements that contribute to high-temperature oxidation resistance include Ni and Cr. Ni itself is an element with high high-temperature oxidation resistance. Cr has the effect of protecting the surface by forming a chromium oxide film on the surface and suppressing oxidation of the material.

[0053] In the heat-resistant alloy of the present invention, since it is composed of approximately equal amounts of Ni and Cr, it is possible for it to have excellent high-temperature oxidation resistance while also having other properties such as high creep rupture strength.

[0054] <Creep rupture strength test> The creep rupture strength of the test pieces at a temperature of 900°C for 1000 hours was measured in accordance with JIS Z 2271. The results are shown in Table 2. The value for Comparative Example 2 was 927°C.

[0055] The creep rupture strength is preferably 20 MPa or more, more preferably 25 MPa or more, and even more preferably 30 MPa or more. Referring to Table 2, it can be seen that all of the inventive examples have creep rupture strengths of 30 MPa or more, which are sufficient creep rupture strengths. On the other hand, Comparative Examples 1 and 2 had low creep rupture strengths. Comparative Example 3 had a creep rupture strength of about 20 MPa.

[0056] <Ammonia exposure test> The test specimen was placed in a furnace tube placed in an electric furnace, and the inside of the furnace tube was replaced with nitrogen gas. The furnace tube was then heated to 600°C, and the atmosphere was replaced with ammonia gas. The test specimen was exposed to ammonia gas for 100 hours and then removed.

[0057] Each of the test pieces taken out was polished in the thickness direction, and the cross section was observed under an optical microscope to measure the thickness of the nitrided layer. The results are shown in Table 2. For reference, a photograph of the cross section of the structure of the test piece of Comparative Example 1 is shown in Figure 1. The part indicated by the reference numeral 10 is the nitrided layer.

[0058] Regarding nitridation, if the thickness of the nitrided layer formed by the ammonia exposure test is 100 μm or less, it can be determined that the nitridation resistance is good. Referring to Table 2, it can be seen that the nitrided layer thickness is 100 μm or less in invention examples 1 to 3 and comparative examples 2 and 3, and the nitridation resistance is excellent. On the other hand, as shown in FIG. 1, in comparative example 1, the nitrided layer 10 is more than 100 μm thick, and the nitridation resistance is poor. Comparing the invention examples, in invention example 3, no nitrided layer is observed, and the nitridation resistance is very good. Although a nitrided layer was formed in invention examples 1 and 2, in invention example 2 it was thin at 22.1 μm, and in invention example 1 it was also less than 100 μm, and the nitridation resistance was good.

[0059] <Creep rupture strength and nitridation resistance> The creep rupture strength of each test piece and the thickness of the nitrided layer formed by the ammonia exposure test were plotted on a graph with the creep rupture strength on the vertical axis and the nitrided layer thickness on the horizontal axis, as shown in Figure 2.

[0060] In the graph of Fig. 2, the further to the upper left the sample, the more excellent both the creep rupture strength and the nitridation resistance. Inventive Examples 1 to 3 are located in the upper left of the graph, and it is clear that they are excellent in creep rupture strength and nitridation resistance. In Fig. 2, the dotted line indicates the range consisting of a nitrided layer thickness of 100 µm or less, which can be determined to have nitridation resistance, and the more desirable lower limit of creep rupture strength of 30 MPa or more. All of the inventive examples are inside the dotted line, and all of the comparative examples are outside the dotted line.

[0061] <<Second Example>> For the test pieces of Inventive Examples 1 to 3 and Comparative Examples 1 and 2 produced in the first embodiment, the activation energy of nitrogen diffusion was derived, and castability and the like were examined.

[0062] <Activation energy> The method for deriving the activation energy of nitrogen diffusion is as described above. The results are shown in Table 3. It was found that all of invention examples 1 to 3 had high activation energies of nitrogen diffusion. In particular, invention example 3 showed a higher value than invention examples 1 and 2. Similarly, comparative example 2 also had a high activation energy of nitrogen diffusion. Table 3 lists the thickness of the nitride layer in the first example, and it can be seen that the higher the activation energy, the thinner the nitride layer.

[0063] [Table 3]

[0064] <Creep rupture strength and activation energy> Figure 3 shows a graph with the vertical axis representing the creep rupture strength and the horizontal axis representing the activation energy of nitrogen diffusion. The creep rupture strength adopted the measured values of the first embodiment (see Table 3). In the graph of Figure 3, the higher it is towards the upper right, the better the creep rupture strength and the higher the activation energy of nitrogen diffusion, thus the better the nitridation resistance. Invention Examples 1 to 3 are located in the upper right of the graph, indicating that they have excellent creep rupture strength and nitridation resistance. In Figure 3, the range of 35 kJ / mol or more, which is the desirable lower limit of the activation energy of nitrogen diffusion that can be judged to have nitridation resistance, and 30 MPa or more, which is a more desirable lower limit of the creep rupture strength, is shown by a dotted line. All of the invention examples are inside the dotted line, and all of the comparative examples are outside the dotted line.

[0065] <Castability> The castability was judged by observing the surface state of the test piece for the fluidity of the molten metal. The evaluation of the castability is in three levels: "○" (good), "△" (ordinary), and "×" (poor). Referring to Table 3, all of Invention Examples 1 to 3 have good castability. This is because carbon and silicon were added in slightly larger amounts. Comparative Example 2 has a relatively high activation energy but is inferior in castability.

[0066] <EPMA Analysis> For the test pieces of Invention Example 1 and Comparative Example 1, the ammonia exposure test of the first embodiment was carried out with the temperature condition changed to 850 °C. Other conditions were the same as those of the first embodiment. For the obtained test pieces, the nitrogen distribution was carried out by EPMA (Electron Probe Micro Analyzer). Figure 4 shows (a) the EPMA image of Invention Example 1 and (b) the EPMA image of Comparative Example 1 respectively. Referring to the figure, the nitrided layer 10 is confirmed in both test pieces (the nitrided layer 10 and the lower part are the test pieces), but it can be seen that the nitrided layer 10 formed in Invention Example 1 is sufficiently thinner than that in Comparative Example 1 because the activation energy of nitrogen diffusion in Invention Example 1 is high.

[0067] The above description is for the purpose of explaining the present invention, and should not be interpreted as limiting the invention described in the claims or restricting the scope of the invention. Furthermore, the configuration of each part of the present invention is not limited to the above embodiment, and various modifications are possible within the technical scope described in the claims.

Claims

1. In mass%, C: 0.2% to 0.6%, Si: more than 0% and not more than 2.5%; Mn: more than 0% and not more than 2.0%; P: 0.03% or less, S: 0.03% or less, Ni: 33.0% to 50.0%, Cr: 24.0% to 50.0%, The balance is Fe and impurities. Optionally, Nb: more than 0% and not more than 1.8%; Optionally, rare earth elements: greater than 0% and not more than 0.5%; Optionally, Ti: more than 0% but not more than 0.5% and / or Zr: more than 0% but not more than 0.5%; Optionally, W: more than 0% to 2.0% and / or Mo: more than 0% to 0.5%; A heat-resistant alloy with excellent nitriding resistance.

2. C: 0.45% to 0.55%, Si: more than 0% and not more than 1.5% Ni: 33.0% to 50.0%, Cr:24.0%~27.0% Nb: more than 0% and 1.0%; 2. A heat-resistant alloy having excellent nitriding resistance according to claim 1.

3. C: 0.4% to 0.6%, Si: more than 0% and not more than 2.0%; Ni: 40.0% to 50.0%, Cr: 24.0% to 38.0%, Nb: 0.5% to 1.8%; 2. A heat-resistant alloy having excellent nitriding resistance according to claim 1.

4. C: 0.2% to 0.5%, Ni: 40.0% to 50.0%, Cr: 30.0% to 50.0%; Optionally, Ti: more than 0% and not more than 0.4%; 2. A heat-resistant alloy having excellent nitriding resistance according to claim 1.

5. The creep rupture strength is 20 MPa or more at 900°C for 1000 hours. A heat-resistant alloy having excellent nitriding resistance according to any one of claims 1 to 4.

6. The activation energy of nitrogen diffusion is 35 kJ / mol or more. A heat-resistant alloy having excellent nitriding resistance according to any one of claims 1 to 4.

7. It is a centrifugally cast body. A heat-resistant alloy having excellent nitriding resistance according to any one of claims 1 to 4.

8. Used in high temperature environments of 500℃ or higher. A heat-resistant alloy having excellent nitriding resistance according to any one of claims 1 to 4.

9. A heat-resistant alloy according to any one of claims 1 to 4, Cracking tube for ammonia gas thermal cracking unit.

Citation Information

Patent Citations

  • C - - - [mechitsukugatareitoukimo[mechitsukugatareitoukimo][tayousurotsutoraina[tayousurotsutoraina]

    JP1975008004A

  • JP1975008005A

  • Cr-ni series heat resistant steel

    JP1991236448A

  • Cr-ni heat resistant steel

    JP1993239599A

  • Corrosion resistant and heat resistant nickel-base casting alloy

    JP1998183282A

Cited By

  • Nickel-chromium casting alloy, use of the alloy, centrifugally casting pipe made from the alloy, method to produce the pipe and use of the pipe

    EP4822046A1